Crosstalk between Wnt/β-Catenin and NF-κB Signaling Pathway during Inflammation - Ma, Bin; Hottiger, Michael O. (Frontiers in Immunology, 2016)
Besides its important role in embryonic development and homeostatic self-renewal in adult tissues, Wnt/β-catenin signaling exerts both anti-inflammatory and pro-inflammatory functions. This is, at least partially, due to either repressing or enhancing the NF-κB pathway. Similarly, the NF-κB pathway either positively or negatively regulates Wnt/β-catenin signaling. Different components of the two pathways are involved in this crosstalk, forming a complex regulatory network. This review summarizes our current understanding of the molecular mechanisms underlying the cross-regulation between the two pathways and discusses their involvement in inflammation and inflammation-associated diseases such as cancer.